2011
DOI: 10.4174/jkss.2011.81.suppl1.s82
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous left external iliac vein rupture

Abstract: We report a 72-year-old female patient with spontaneous rupture of the left external iliac vein. She visited our hospital for abdominal and back pain. She had the abnormal finding of hemoperitoneum. We performed an emergency operation with diagnosis of left ovarian cyst rupture though she suffered from spontaneous rupture of the left external iliac vein. This case provides insight to the experience of spontaneous rupture of the left external iliac vein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 5 publications
(5 reference statements)
0
22
0
Order By: Relevance
“…Because hypovolaemic shock is the chief clinical sign, emergency exploratory surgery is required in most cases of rupture of the iliac vein. However, most cases in the literatures were operated under the misdiagnosis of a ruptured aortic aneurysm or emergency of unknown causes [11,20]. CT might play an important role in this regard.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because hypovolaemic shock is the chief clinical sign, emergency exploratory surgery is required in most cases of rupture of the iliac vein. However, most cases in the literatures were operated under the misdiagnosis of a ruptured aortic aneurysm or emergency of unknown causes [11,20]. CT might play an important role in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…The rupture of an iliac vein is rare, life-threatening, and it mostly results from trauma or injury during pelvic surgery. Spontaneous rupture of the iliac vein is even more unusual, and most cases were diagnosed only intraoperatively and surgery was often associated with substantial mortality and morbidity [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Only Cho et al reported successful conservative treatment of spontaneous rupture of the left common iliac vein [14].…”
Section: Introductionmentioning
confidence: 99%
“…Another study also reported that obstruction of flow or vibratory irritation may lead to vessel weakening [ 3 ]. Inflammatory factors such as thrombophlebitis or DVT may also affect the elasticity of the vessel wall [ 1 , 2 ]. On the other hand, estrogen in females may play a role to protect the vessels and promote compliance [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous iliac vein rupture (SIVR) is a rare entity with only three cases having been documented in Korea [ 1 , 2 ]. However, clinical suspicion and early diagnosis of SIVR is very important since it may be life-threatening, often requiring aggressive management of unstable vital signs and emergent operation.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, less than 45 patients have been reported. 1 7 Most of the patients were middle-aged women; in fact, only one case report has described a male patient. 1,7 The concomitant disease includes deep vein thrombosis (DVT) and thrombophlebitis.…”
Section: Introductionmentioning
confidence: 99%